Fiscal Decentralization Reform and its Impacts on Primary Education Service Delivery in Tanzania: the Case of Dodoma Municipal Council - Paul MTASIGAZYA (Ученые записки Института Африки Российской академии наук)
This study is about fiscal decentralization reforms implemented in Local Government Authorities (LGAs) in Tanzania with special focus on Primary Education Service Delivery in Dodoma Municipal Council. The study investigated the question of poor performance of the municipal council in primary education service delivery despite the reforms undertaken to devolve the finances and functions to the council. It aimed to find out the extent and manner the fiscal decentralization has been implemented and its effects on the council’s performance on primary education service delivery. The study is based on data collected through interview and documentary review. It has been observed that despite to fiscal decentralization reforms, still there has been no significant improvement in quantitative and qualitative primary education service delivery in the council. This study further noted that the practice of fiscal decentralization such as intergovernmental fiscal transfer, (grants) and local government own sources of revenues are not adequate. The devolved funds also are characterized by conditional ties which undermine the autonomy and priorities of the Council. The study also noted that financial capacity of the council is weak despite the reform which have not provided for the expenditure on school infrastructure, furniture and poor academic performance to standard seven examinations and inadequate funds disbursed to the council, have led to poor primary education service delivery. The study recommends that council should be assured of autonomy in fiscal control and management to ensure qualitative and quantitative primary education service delivery.